B cell-based therapies in CNS autoimmunity: differentiating CD19 and CD20 as therapeutic targets - Thomas G. Forsthuber (Therapeutic Advances in Neurological Disorders, 2018)
Increasing recognition of the role of B cells in the adaptive immune response makes B cells an important therapeutic target in autoimmunity. Numerous current and developmental immunotherapies target B cells for elimination through recognition of cell-surface proteins expressed specifically on B cells, in particular CD19 and CD20. Similarities and differences in the function and expression of these two molecules predict some shared, and some distinct, pharmacological effects of agents targeting CD19 versus CD20, potentially leading to differences in the clinical safety and efficacy of such agents. Here, we review current knowledge of CD19 and CD20 function and biology, survey current and developmental therapies that target these molecules, and discuss potential differences in elimination of B cells by drugs that target CD19 versus CD20, with particular focus on the central nervous system autoimmune diseases multiple sclerosis and neuromyelitis optica. The principles and mechanisms herein discussed might also be relevant to a variety of other nervous system autoimmune disorders, including NMDA (N-methyl-D-aspartate) receptor encephalitis, transverse myelitis and myasthenia gravis.